A Facile Microwave-Promoted Formation of Highly Photoresponsive Au-Decorated TiO2 Nanorods for the Enhanced Photo-Degradation of Methylene Blue - Andreea Bondarev; Sonia Mihai; Abubakar Katsina Usman; Diana Luciana Cursaru; Dănuţa Matei; Veronica Sătulu; Cătălina Gheorghe; Gheorghe Brănoiu; Raluca Şomoghi (Nanomaterials)
The integration of noble metal nanoparticles (NPs) effectively modifies the electronic properties of semiconductor photocatalysts, leading to improved charge separation and enhanced photocatalytic performance. TiO2 nanorods decorated with Au NPs were successfully synthesized using a cost-effective, rapid microwave-assisted method in H2O2 and HF media for methylene blue (MB) degradation under visible light illumination. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), N2 physisorption, and UV–vis spectroscopy were employed to characterize the structures, morphologies, compositions, and photoelectronic properties of the as-synthesized materials. The fusing of Au NPs effectively alters the electronic structure of TiO2, enhancing the charge separation efficiency and improved electrical conductivity. The HF treatment promotes the exposure of the highly reactive (001) and (101) crystalline facets. The improved photocatalytic activity of Au/TiO2, achieving 97% efficiency, is attributed to the surface plasmon resonance (SPR) effect of the Au NPs and the presence of oxygen vacancies. The photodegradation of MB using the TiO2/Au photocatalysts follows pseudo-first-order kinetics, highlighting the enhanced catalytic efficiency of the synthesized nanostructures. The exceptional properties of the binary Au/TiO2 photocatalysts, including the SPR effect, exposed crystallographic faces, and efficient charge carrier separation through a decrease in the recombination of electrons and holes, contribute to the photocatalytic degradation of MB.